Evaluation of modified Alvarado scoring system in acute appendicitis at Vydehi Institute of Medical Sciences and Research Centre, Bangalore, Karnataka, India - Rithin, Punjala Sai; Agarwal, Aman; Budigi, Bhavana (International Surgery Journal, 2017)
Background: Despite of much advancement in modern diagnostic technology, decision making in patients with acute appendicitis is still a challenge worldwide. Many diagnostic scoring systems have been developed. Of them modified Alvarado scoring system (MASS) has been reported to be a cheap and quick diagnostic tool which minimizes negative appendectomy rate. The present study was aimed to evaluate the efficacy of MASS in diagnosing acute appendicitis and correlating the same with histopathological results. Methods: This prospective cohort study conducted from November 2012 to April 2014, over a period of 18 months at Vydehi Institute of Medical Sciences and Research Centre, Bangalore. 100 patients with symptoms of acute appendicitis were enrolled in the study. They were diagnosed using MASS. Patients with a score of 7 to 10 were taken up for surgery. Patients with a score below 7, but with high suspicion of acute appendicitis by the surgeon were taken up for surgery. Following surgery all appendix specimens were sent for histopathologic examination. Results: A total number of 100 patients were participated in the study. Of them patients under the age group of 21-30 years were more affected with acute appendicitis (51%). Male predominance was observed in the study (74%). The common symptom observed in all patients (100%) was tenderness in right Iliac fossa (RIF). Out of 100 patients, 79% of the patients were presented with a modified Alvarado score of ≥7 and 21% presented with a score of <7. The sensitivity and specificity of the MASS in this study was 89.66% and 92.31% in both males and females respectively. The positive predictive value was 98.73%, negative predictive value was 57.41% and the NAR was 6.75% and 30.76% in male and female patients respectively. Conclusions: The observations of the study confirm that use of MASS in patients suspected to have acute appendicitis provides a high degree of diagnostic accuracy and subsequently reduces the negative appendicectomy and complication rates.